A Contagious... Smile! Training Emotional Skills of Adults with Intellectual Disability in the Time of COVID-19 - Maria Elide Vanutelli; Antonella Grieco; Eleonora Comelli; Claudio Lucchiari (MDPI AG, 2023)
The COVID-19 emergency has had important implications not only for physical but also for psychological well-being. This is particularly true for fragile populations such as people with intellectual disability (ID), who are particularly at risk of suffering during uncertain times. The goal of this action research was to design, implement, and test the efficacy of emotional competencies training to support people with ID in coping with stressful events. For this purpose, eight adults with ID followed a 5-week training of increasing complexity, aimed at exercising different skills through group activities. We designed a study to test its feasibility and efficacy, using both quantitative and qualitative methods. The analyses revealed that, after the training, participants used a more complex emotional language and were able to frame their perception of COVID-related threat with greater confidence and awareness. These findings, although circumscribed, respond positively to the urgent need to develop emotional support programs targeted at people with ID.